2019
DOI: 10.29252/jpm.6.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Effect of client-centered therapy on PTSD and depression in raped women in Bandar Abbas

Abstract: Introduction: POSTD and depression are psychosomatic disorders that can be manifested as a result of rape and are a major threat to the health of victims. The aim of this study was to determine the effectiveness of Client-Centered Therapy on PTSD and depression in raped women in Bandar Abbas. Methods: The statistical population of the study was 30 female victims of rape in the age group of 13-30 years who referred to psychology, counseling, and welfare offices of Bandar Abbas in 1396. The subjects were selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…This study is in line with the findings of Saad et al (2014), who found that the groups who received person‐centred or cognitive psychology add‐in counselling showed significant reductions (pretest to post‐test) in depression, which enhanced the self‐concept and resilience of pregnant out‐of‐wedlock teenagers. This result conforms to the findings of Hashemi Pour and Bahreinian (2019), whose results of a multivariate covariance analysis showed that the client‐centred treatment improved participants’ depression and psychological stress on multiple aspects of post‐traumatic stress disorder (PTSD; p < 0.05). These findings suggest that CCT is effective for PTSD and depression.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This study is in line with the findings of Saad et al (2014), who found that the groups who received person‐centred or cognitive psychology add‐in counselling showed significant reductions (pretest to post‐test) in depression, which enhanced the self‐concept and resilience of pregnant out‐of‐wedlock teenagers. This result conforms to the findings of Hashemi Pour and Bahreinian (2019), whose results of a multivariate covariance analysis showed that the client‐centred treatment improved participants’ depression and psychological stress on multiple aspects of post‐traumatic stress disorder (PTSD; p < 0.05). These findings suggest that CCT is effective for PTSD and depression.…”
Section: Resultssupporting
confidence: 90%
“…In organisations, secondary and tertiary institutions around the world, numerous researchers have undertaken studies on CCT on educational, vocational and personal–social concerns. A number of them (Bondestam & Lundqvist, 2020; Elliott, 2016; Hashemi Pour & Bahreinian, 2019; Jones, 2020; Park, 2018; Saad et al, 2014) found CCT to be very effective. This study assumes that CCT will, to some extent, address SH problems in tertiary institutions in Taraba State, Nigeria.…”
Section: Introductionmentioning
confidence: 99%